Holistic Management of Schizophrenia Symptoms Using Pharmacological and Non-pharmacological Treatment - Ganguly, Pronab; Soliman, Abdrabo; Moustafa, Ahmed A. (Frontiers in Public Health, 2018)
Individuals with schizophrenia lead a poor quality of life, due to poor medical attention, homelessness, unemployment, financial constraints, lack of education, and poor social relationships. Thus, a review of factors associated with the holistic management of schizophrenia is of paramount importance. The objective of this review is to improve the quality of life of individuals with schizophrenia, by addressing the factors related to the needs of the patients and present them in a unified manner. Although medications play a role, other factors that lead to a successful holistic management of schizophrenia include addressing the following: financial management, independent community living, independent living skill, relationship, friendship, entertainment, regular exercise for weight gained due to medication administration, co-morbid health issues, and day-care programmes for independent living. This review discusses the relationship between different symptoms and problems individuals with schizophrenia face (e.g., homelessness and unemployment), and how these can be managed using pharmacological and non-pharmacological methods. Thus the target of this review is the carers of individuals with schizophrenia, public health managers, counsellors, case workers, psychiatrists, and clinical psychologists aiming to enhance the quality of life of individuals with schizophrenia.